The Portrait of Islamic Education Online Learning during the Covid-19 Pandemic in MAN 1 Ternate - Adam, Adiyana; Soleman, Noviyanti (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
The advent of online learning for Islamic education can be attributed to the global impact of the Coronavirus Disease 2019 (Covid-19) pandemic. Islamic education is a significant field of study that plays a pivotal role in fostering the personal dignity of individuals through the guidance of Islamic principles and teachings. However, the pandemic has introduced a number of challenges that have an impact on the effectiveness of online learning for Islamic education. The objective of this study is to ascertain the circumstances prevailing in Indonesia with regard to the online teaching of Islamic Education, with a particular focus on Madrasah Aliyah Negeri 1 Ternate. The researchers employed a qualitative methodology and a phenomenological approach, which was further elucidated through field research. The data employed in this study are primary and secondary data obtained directly from the research site, namely MAN 1 Ternate, as well as from a number of studies on the online learning of Islamic education in Indonesia. The findings of the study indicate that the institution in Indonesia has not yet achieved the desired effectiveness of online learning of Islamic education. Similarly, this is also the case at MAN 1 Ternate, where online learning of Islamic education is not yet considered to be adequate. This is due to the fact that the level of understanding among students is not yet optimal, despite the sufficient preparation of teachers.